Carbide sludge management in acetylene producing plants by using vacuum filtration - Ramasamy, P.; Ibrahim, Shaliza; Agamuthu, Pariatamby (SAGE Publications (UK and US), 2002)
Carbide sludge (10.4-11.5 tonnes day -1) is generated from the reaction of calcium carbide (900 kg) and water (6,000 L) in the production of acetylene (2400 m 3), in three selected acetylene manufacturing plants. The sludge (of pH 12.2 and containing Cu, Ph, Fe, Mn, Ni and Zn ions whose concentrations exceed the Department of Environment limits for industrial wastewater) was treated by vacuum filtration as a substitute for the ponding system, which is environmentally less acceptable. A similar system by flocculation was also developed. The filtration system represents an improvement over the ponding method, as shown by a pH of 7 for the clear filtrate; the solid cake, which contains 98% of the metals, can be conveniently disposed at an integrated scheduled waste treatment centre.